African Suid Genomes Provide Insights into the Local Adaptation to Diverse African Environments. (22nd November 2022) - Xie, Hai-Bing; Yan, Chen; Adeola, Adeniyi C; Wang, Kun; Huang, Cui-Ping; Xu, Ming-Min; Qiu, Qiang; Yin, Xue; Fan, Chen-Yu; Ma, Yun-Fei; Yin, Ting-Ting; Gao, Yun; et al.
Abstract: African wild suids consist of several endemic species that represent ancient members of the family Suidae and have colonized diverse habitats on the African continent. However, limited genomic resources for African wild suids hinder our understanding of their evolution and genetic diversity. In this study, we assembled high-quality genomes of a common warthog ( Phacochoerus africanus ), a red river hog ( Potamochoerus porcus ), as well as an East Asian Diannan small-ear pig ( Sus scrofa ). Phylogenetic analysis showed that common warthog and red river hog diverged from their common ancestor around the Miocene/Pliocene boundary, putatively predating their entry into Africa. We detected species-specific selective signals associated with sensory perception and interferon signaling pathways in common warthog and red river hog, respectively, which contributed to their local adaptation to savannah and tropical rainforest environments, respectively. The structural variation and evolving signals in genes involved in T-cell immunity, viral infection, and lymphoid development were identified in their ancestral lineage. Our results provide new insights into the evolutionary histories and divergent genetic adaptations of African suids.